MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN PENDEKATAN STEAM DI SEKOLAH DASAR - Kartikasari; Herlina Usman; Resi Ratna Suminar; Nuryani (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to improve the learning outcomes of mathematics students in grades VI (SDN Kampungsawah 01, District Rumpin) with this type of action research. The subjects in this study were sixth grade students at SDN Kampungsawah 01 for the academic year 2022–2023, with a total of 28 students, consisting of 10 male students and 18 female students. Data obtained through tests, observations, and documentation Data analysis techniques using qualitative descriptive analysis According to the data analysis results, there was an increase in learning management by teachers, learning activities, and student learning outcomes from cycles I, II, and III, with each cycle obtaining the value of aspects of learning management by teachers in the observation phase at intervals of 2.12 with a predicate of